La Forge Céleste. Gaston Bachelard et Giacinto Scelsi - Solares, Blanca (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
Our culture, focused on sight rather than sound, has set aside listening as a human faculty of knowledge and sound as a sphere of significance. The result has been the homogenization of listening, the growing pollution of the auditory environment and the regrettable reduction of music to musical pastiche, cacophonic backdrop or entertainment media and commercial spectacle. It is in the light of this devastating social and ecological auditory crisis that the work of Gaston Bachelard opens up an unusual field of research in the field of human sciences. We are going to link here his ideas on the sound imagination of matter with the investigations on the sound of the brilliant Italian composer Giacinto Scelsi.